Emission Color Trajectory and White Electroluminescence Through Supramolecular Control of Energy Transfer and Exciplex Formation in Binary Blends of Conjugated Polyrotaxanes - Brovelli, S; Sforazzini, G; Serri, M; Winroth, G; Suzuki, K; Meinardi, F; Anderson, H; Cacialli, F (2012)
White electroluminescence and fine-tuning of the emission color from binary blends of a blue-emitting polymer and a green/yellow-emitting threaded molecular wire consisting of a conjugated polymer supramolecularly encapsulated by functionalized cyclodextrins are demonstrated. Encapsulation controls the minimum intermolecular distance on the nanoscale, resulting in suppressed energy-transfer between the blend constituents and reduced formation of interchain charge-transfer complexes. The use of a green-emitting polyrotaxane significantly improves the electrical properties with respect to blends of a blue electroluminescent polyrotaxane and leads to a significant reduction in the turn-on voltage required for achieving white electroluminescence (V ON = 3V), with only 20% by weight of the encapsulated material. Blends of a blue-emitting polymer and a green/yellow-emitting threaded molecular wire emit white luminescence due to control of the minimum intermolecular distance at the nanoscale, which results in suppressed energy transfer between the blend constituents and reduced formation of interchain charge-transfer complexes. Light-emitting diodes incorporating only 20% by weight of the encapsulated material display white electroluminescence with a turn-on voltage of just 3 V. Copyright © 2012 WILEY-VCH Verlag GmbH and Co. KGaA, Weinheim.